2018
DOI: 10.5468/ogs.2018.61.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Safety of delayed umbilical cord clamping in preterm neonates of less than 34 weeks of gestation: a randomized controlled trial

Abstract: ObjectiveThere is concern regarding the safety of delayed cord clamping (DCC) in babies born at less than 34 weeks' gestation. Therefore, the primary objective of this study was to compare the rates of hyperbilirubinemia and polycythemia during initial 7 days in infants born at less than 34 weeks' gestation and randomized to receive DCC by 120 seconds or early cord clamping (ECC) within less than 30 seconds.MethodsOne hundred pregnant women were randomly subjected to DCC or ECC at the time of birth in a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Most studies included infants of <34 weeks’ gestational age, and most were done in high-income countries. 188–210…”
Section: Neonatal Life Supportmentioning
confidence: 99%
“…Most studies included infants of <34 weeks’ gestational age, and most were done in high-income countries. 188–210…”
Section: Neonatal Life Supportmentioning
confidence: 99%
“…Fifty-six randomized clinical trials enrolling 6852 infants were included. The characteristics of the included studies are summarized in the Table . Eight studies were published in the Chinese language .…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies compared DCC with ICC, of which 1 study reported neurodevelopmental outcomes . Among these studies, the duration of DCC ranged from at least 30 seconds to more than 180 seconds.…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow is shown in online supplementary Figure 1. Of the included RCTs, 18 enrolled 2,253 newborns born at <34 weeks of gestation [25, 27-33, 36, 38, 41, 43-45, 47-50] and 9 enrolled 883 LPT newborns [24, 26, 34, 35, 37, 39, 40, 42, 46]. Intransitivity was assessed by comparing the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 included RCTs, 7 had a low ROB [25, 26, 36, 38, 39, 42, 45]. While 6 RCTs had some concerns [27, 31, 33, 37, 40, 43], 14 had a high ROB [24, 28-30, 32, 34, 35, 41, 44-50].…”
Section: Resultsmentioning
confidence: 99%